TEKNOLOGI MOTION-BASED TRACKING UNTUK PENGEMBANGAN APLIKASI KEAMANAN - Mira Orisa; Karina Auliasari; Rofila El Maghfiroh (Jurnal Teknologi Informasi dan Terapan, 2019)
The surveillance camera system is widely used by the public. The surveillance camera system used is usually a CCTV camera. In general, CCTV cameras can only record video. Security monitoring or monitoring by CCTV cameras can only be effective if there are operators who see the record directly on a monitor. Actually the surveillance camera system can be programmed to give a warning sign to the user. The surveillance camera used in this study is the IP camera. The camera is a camera that can be programmed to provide a notification to the user. By implementing motion-based tracking technology on the surveillance camera system can detect movement. Kalman filter is one of the motion-based tracking methods. Kalman filters can predict the movements recorded by the IP camera. The results of this study state that the surveillance camera system can provide notification messages to users via an android device when the surveillance camera records the movement of human objects.